2010
DOI: 10.1155/2010/364957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifestyle Measures, Antiobesity Agents, and Bariatric Surgery on Serological Markers of Inflammation in Obese Patients

Abstract: Overweight and obesity are highly prevalent in developed countries and are also becoming more frequent in the developing world. Overweight and obese patients have elevated levels of several inflammatory markers and this inflammatory state might contribute to their increased vascular risk. We summarize the effects of lifestyle changes, antiobesity agents, and bariatric surgery on serological inflammatory markers in overweight and obese patients. Most studies showed a decrease in inflammation with all 3 interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 196 publications
(300 reference statements)
1
11
0
2
Order By: Relevance
“…Nevertheless, significant weight reduction via change in diet (Breum et al , 2003) or bariatric surgery (Brandacher et al , 2006) has not been shown to restore tryptophan balance. This in part may be related to a relative lack of change in inflammatory factors after rapid weight loss (Brandacher et al , 2006), although more delayed responses may be seen (Tziomalos et al , 2010). Therefore, the immune activation found in obesity may contribute to the same diversion of tryptophan metabolism from serotonin to kynurenine, which could contribute to depression.…”
Section: 0 Inflammation and Depressionmentioning
confidence: 99%
“…Nevertheless, significant weight reduction via change in diet (Breum et al , 2003) or bariatric surgery (Brandacher et al , 2006) has not been shown to restore tryptophan balance. This in part may be related to a relative lack of change in inflammatory factors after rapid weight loss (Brandacher et al , 2006), although more delayed responses may be seen (Tziomalos et al , 2010). Therefore, the immune activation found in obesity may contribute to the same diversion of tryptophan metabolism from serotonin to kynurenine, which could contribute to depression.…”
Section: 0 Inflammation and Depressionmentioning
confidence: 99%
“…90 Inflammatory mediators (hs-CRP, IL-6, IL-18) As mentioned above, obese PCOS patients have high levels of proinflammatory mediators, such as high sensitive C-reactive protein (hs-CRP), interleukin 6 (IL-6) and IL-18, which make them vulnerable to an increased risk of non-alcoholic fatty liver disease (NAFLD). 91 C-reactive protein (hs-CRP), one of the acute phase proteins known as a vascular inflammatory marker, rises dramatically in response to inflammation due to an increase in the circulating level of interleukin 6 (IL-6), which is produced mainly by macrophages and adipocytes. The level of hs-CRP is significantly elevated in PCOS patients.…”
Section: Leukotriene Metabolism Related Genes Alox15 Fem1a Fem1bmentioning
confidence: 99%
“…91 C-reactive protein (hs-CRP), one of the acute phase proteins known as a vascular inflammatory marker, rises dramatically in response to inflammation due to an increase in the circulating level of interleukin 6 (IL-6), which is produced mainly by macrophages and adipocytes. The level of hs-CRP is significantly elevated in PCOS patients.…”
mentioning
confidence: 99%
“…obesity reviews Adipose tissue, triglycerides and atherosclerosis A. P. van de Woestijne et al 835 lifestyle factors such as diet, physical activity and weight reduction, is of vital importance in these patients. Besides lifestyle measures, anti-obesity agents and bariatric surgery have all been reported to reduce inflammatory markers, indicating improved adipose tissue function (79).…”
Section: Management Of Obesity-induced Hypertriglyceridemiamentioning
confidence: 99%